O processo de elaboração de saberes por professores-pesquisadores de educação física em uma comunidade colaborativa - Sanches Neto, Luiz [UNESP] (2014)
In the educational theories and public policies oriented towards professionalization of teaching, traversing the notion of teaching professionalism, it is expected that teachers who work in basic education develop their own knowledge in a process of ongoing formation. However, there seems to be some notion of dependency of such teachers to specialists as the theoretical and methodological contributions indicate that mediation between school and university should fit the academic researcher. However, the concept of teacher-researcher could indicate progress in the dimension of thinking beyond the division between school teachers' research and academic researchers. There is the assumption that the practice engenders an epistemology, leaving us - teachers, professors and researchers - to unveil it. Therefore, the general objective is to understand the process of knowledge elaboration by teachers while researching their own teaching practice. It aims to investigate how teachers do organize the teaching and research in relation to school physical education. Thus, the specific objective refer to: identify how teachers organize the teaching and research based on shared knowledge within a permanent and collective process of professional education and development. The qualitative methodological procedures involved collaboration with a group of physical education teachers who reflect collectively on their teaching practices in a kind of autonomous community of teachers. We invited twelve teachers from such community to participate in our research. We have proposed the following techniques to generate and analyze data: documentary source, semi-structured interviews, focus groups, and content analysis. Results indicated that the participants emphasized influence from academic and family relationships in their personal elaboration of knowledge. Towards the research mode, the participants shared predominantly notions on action-research, and...